(untitled) (Alternautas, 2022)
Buen Vivir, as an alternative concept to development (Acosta 2012, Cubillo-Guevara & Hidalgo-Capitán 2015a), emerged in Ecuador at the beginning of the 1990s, with the contribution of some Amazonian Kichwa intellectuals, under the name of sumak kawsay (Viteri et al. 1992, Viteri 1993, Viteri 2000, Cubillo-Guevara & Hidalgo-Capitán 2015b); however, it did not gain relevance until the 2008 Ecuadorian Constitutions included it as a principle (Vanhulst and Beling 2016). This concept has been defined as a way of life in harmony with oneself (identity), with society (equity) and with nature (sustainability) (Cubillo-Guevara, Hidalgo-Capitán & García-Álvarez 2016). This definition was commonly accepted by the majority of intellectuals and politicians who used the term since the drafting of the 2008 Constitution; but here the consensus ended, since this way of living in harmony took on very different meanings according to the ideological position of each intellectual and politician who used the concept. Thus, there have been at least three ways of understanding Buen Vivir in Ecuador: one indigenist, another socialist and another ecologist / post-developmentalist (Le-Quang & Vercoutère 2013, Cubillo-Guevara, Hidalgo-Capitán & Domínguez-Gómez 2014, Vanhulst 2015).